Pengaruh Budaya Organisasi dan Disiplin Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada Karyawan Bagian Produksi PT. Nyonya Meneer Semarang) - Estetika Arumsari Agustin; Sudharto Prawata Hadi; Widiartanto Widiartanto (Universitas Diponegoro, 2015)
Employee performance can determine the success of a company. Several factors influencing employee performance are organizational cuture and work discipline. PT. Nyonya Meneer Semarang is a company which engaged in traditional medicine industry. The problem of this research is the decreased of production over the last four years and did not achieve the production targets. It indicates that the employee performance is still not maximized.The purpose of this study is to identify the influence of organizational culture and work discipline to employee performance. This type of study is explanatory research using questionnaires, interview and study literature as method of data collection. This study used 79 respondents of production employee which choosen by probability sampling technique (simple random sampling). Data analysis which used in this study are simple linear regression, multiple linear regression, correlate analysis, t test and f test with SPSS.According to the study results, organizational culture and work discipline influence on employee performance. Organizational culture has influenced 0,392 to employee performance and work discipline has influenced 0,242 to employee performance. Simultaneously, organizational culture and work discipline has contributed 0,410 to employee performance.The conclusion shows that organizational culture and work discipline either partially or simultaneously influence the performance of production employee of PT. Nyonya Meneer Semarang. Based on these results, PT. Nyonya Meneer Semarang should be able to improve the organizational culture, especially in the communication between employee and management. In addition, PT. Nyonya Meneer Semarang is expected to improve the quality of control or supervision to maintain and improve the discipline of employees, and make further research to find out the influence from other variables.